Targeting the Gut Microbiota in Chagas Disease: What Do We Know so Far? - Duarte-Silva, Eduardo; Morais, Livia H.; Clarke, Gerard; Savino, Wilson; Peixoto, Christina (Frontiers in Microbiology, 2020)
Chagas disease (CD) is a tropical and still neglected disease caused by Trypanosoma cruzi (T. cruzi) that affects > 8 million of people worldwide. Although limited, emerging data suggest that gut microbiota dysfunction may be a new mechanism underlying CD pathogenesis. T. cruzi-infection leads to changes in the gut microbiota composition of vector insects, mice and humans. Alterations in insect and mice microbiota due to T. cruzi have been associated with a decreased immune response against the parasite, influencing the establishment and progression of infection. Further, changes in the gut microbiota are linked with inflammatory and neuropsychiatric disorders, comorbid conditions in CD. Therefore, this review article critically analyses the current data on CD and the gut microbiota of insects, mice, and humans and discusses its importance for CD pathogenesis. An enhanced understanding of host microbiota will be critical for the development of alternative therapeutic approaches to target CD, such as gut microbiota-directed interventions.